Circadian timing of metabolism in animal models and humans. (6th February 2015) - Dibner, C.; Schibler, U.
Abstract Most living beings, including humans, must adapt to rhythmically occurring daily changes in their environment that are generated by the Earth's rotation. In the course of evolution, these organisms have acquired an internal circadian timing system that can anticipate environmental oscillations and thereby govern their rhythmic physiology in a proactive manner. In mammals, the circadian timing system coordinates virtually all physiological processes encompassing vigilance states, metabolism, endocrine functions and cardiovascular activity. Research performed during the past two decades has established that almost every cell in the body possesses its own circadian timekeeper. The resulting clock network is organized in a hierarchical manner. A master pacemaker, located in the suprachiasmatic nucleus (SCN) of the hypothalamus, is synchronized every day to the photoperiod. In turn, the SCN determines the phase of the cellular clocks in peripheral organs through a wide variety of signalling pathways dependent on feeding cycles, body temperature rhythms, oscillating bloodborne signals and, in some organs, inputs of the peripheral nervous system. A major purpose of circadian clocks in peripheral tissues is the temporal orchestration of key metabolic processes, including food processing (metabolism and xenobiotic detoxification). Here, we review some recent findings regarding the molecular and cellular composition of the circadian timing system and discuss its implications for the temporal coordination of metabolism in health and disease. We focus primarily on metabolic disorders such as obesity and type 2 diabetes, although circadian misalignments (shiftwork or 'social jet lag') have also been associated with the aetiology of human malignancies.